2014
DOI: 10.1371/journal.ppat.1004340
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Signal Transduction Pathway that Modulates rhl Quorum Sensing and Bacterial Virulence in Pseudomonas aeruginosa

Abstract: The rhl quorum-sensing (QS) system plays critical roles in the pathogenesis of P. aeruginosa. However, the regulatory effects that occur directly upstream of the rhl QS system are poorly understood. Here, we show that deletion of gene encoding for the two-component sensor BfmS leads to the activation of its cognate response regulator BfmR, which in turn directly binds to the promoter and decreases the expression of the rhlR gene that encodes the QS regulator RhlR, causing the inhibition of the rhl QS system. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(133 citation statements)
references
References 80 publications
(155 reference statements)
10
123
0
Order By: Relevance
“…To identify genetic factors that govern rhamnolipid production in P. aeruginosa , we performed a screen for rhamnolipid defective mutants using a library of PAO1:: rhlA ‐ lacZ (Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/mmi.12954/suppinfo) transposon mutants and a methylene blue/cetyltrimethylammonium bromide (CTAB) agar plate method (Kohler et al ., ; Gupta et al ., ; Cao et al ., ). Approximately 50 000 transposon insertion mutants were visually analyzed by scoring the severe decrease in the size of the blue halo surrounding the bacterial colonies on the CTAB agar plates, which indicates the production of rhamnolipid (Kohler et al ., ; Gupta et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…To identify genetic factors that govern rhamnolipid production in P. aeruginosa , we performed a screen for rhamnolipid defective mutants using a library of PAO1:: rhlA ‐ lacZ (Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/mmi.12954/suppinfo) transposon mutants and a methylene blue/cetyltrimethylammonium bromide (CTAB) agar plate method (Kohler et al ., ; Gupta et al ., ; Cao et al ., ). Approximately 50 000 transposon insertion mutants were visually analyzed by scoring the severe decrease in the size of the blue halo surrounding the bacterial colonies on the CTAB agar plates, which indicates the production of rhamnolipid (Kohler et al ., ; Gupta et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Given that the expression of rhlAB is controlled by the rhl QS system (Brint and Ohman, ; Ochsner and Reiser, ), we next sought to determine whether the crc deletion alters the level of the rhl QS signal C4‐HSL content. We measured the content of the RhlI‐dependent autoinducer C4‐HSL in a wild‐type PAO1 strain, a Δ crc strain and a complementary strain (Δ crc /p‐ crc ) when bacteria were grown in M8 minimal medium, using the pDO100 (pKD‐ rhlA ) system (Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/mmi.12954/suppinfo) that carries a lux reporter fused with an rhlA promoter (Liang et al ., ; Cao et al ., ). We observed that the supernatants prepared from either the wild‐type PAO1 strain or the complemented strain (Δ crc /p‐ crc ), but not the Δ crc strain, markedly promoted luminescence values (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The RHL system acts through C4-HSL (N-butanoylhomoserine lactone), responsible for the production ramnolipids and elastase. The LAS and RHL systems are still modulated by a quinolone, 2-heptyl-3-hydroxy-4-quinolone, called PQS, which increases the complexity of QS network [87,88].…”
Section: Biofilm and Quorum Sensingmentioning
confidence: 99%